THEORETICAL BASES OF EFFECTIVE MANAGEMENT OF HUMAN CAPITAL IN THE CONDITIONS OF INNOVATIVE DEVELOPMENT OF ENTERPRISES - Olimova Nargizahon Odilbek kizi (Scholar Express Journals, 2022)
The article informs that in the current situation, the tasks of innovative development of the economy are in the forefront, and the formation of innovations as a determinant of competitiveness at all levels is a requirement of the times. It is important to further increase the innovative activity of enterprises that have become leaders in ensuring the innovative development of our country. For this purpose, the development of human capital in our country, what indicators should be taken into account in the calculation of the human capital index
Keywords: Innovation; Human Capital; Human Factor; Social Welfare